The Effect of Confucianism on Future Birth Rates in South Korea and Japan - Flora Arifahsasti; Kurniawaty Iskandar (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
South Korea and Japan adhere to Confucianism as the foundation of significant values and norms in their social systems. Confucianism is closely related to the patriarchal system, which makes it difficult for women in South Korea and Japan to prosper and get the right to a decent job because it only addresses women as “servants of the family.” The gender prejudice experienced by these women created the Shampoo generation in South Korea and the Satori generation in Japan. This article seeks to answer the question, “How did South Korean and Japanese women start the liberal feminist trend movement based on self-rationality?”  The author analyzed data from South Korean and Japanese women who act self-rationally by refusing to marry and have children using qualitative research methods and rational choice theory. So, with declining birth rates, the tendency of this generation of Shampoo and Satori ultimately threatens the demographic stability of the country and will threaten the country’s future.